Epistemological and Ethical Philosophy of Mathematics In 21st Century Mathematics Learning Practices - Himmi, Nailul; Dewi, Izwita; Ahyaningsih, Faiz (Universitas Wiralodra, 2023)
21st century mathematics education has made use of science and technology while maintaining the philosophy of mathematics from an ethical and epistemological standpoint. This paper examines the goals of the philosophy of mathematics from an epistemological and ethical perspective. It also investigates the relationship between these perspectives and the practice of studying mathematics in the twenty-first century. This article was written using the Publish or Perish software and a systematic literature review approach. 41 initial articles were found by inputting keywords. Following review, fifteen articles were found to be in agreement. This study reveals that the goal of mathematics philosophy is to understand truth, meaning, certainty, and the nature and sources of mathematical knowledge, as well as how to interpret mathematics, from an epistemological perspective. Analyze and reflect on the ethical implications of mathematical practices. Its epistemological application in 21st century learning practices guides the way concepts are positioned, logical arguments are made, and mathematical problems are solved. Next, ethical considerations include maintaining student privacy, establishing learning agreements in every class, and avoiding creating group distinctions. by utilizing an interactive, student-centered learning paradigm like PBL, inquiry, contextual learning, use of technology, STEM, and others. Such behaviors will subsequently cultivate the values of critical, communicative, creative, and cooperative character. Therefore, we must uphold the fundamentals of learning in the 21st century, both in terms of epistemology and ethics.